2017
DOI: 10.1111/ijfs.13532
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the phenolic contents and antioxidant activities of citrus peels from different cultivars after in vitro digestion

Abstract: The aim of this study was to investigate the effects of in vitro digestion on the phenolic contents and antioxidant activities of citrus peels. Three different varieties of citrus peels (mandarin, ponkan and red tangerine) were treated with simulated gastric fluid (SGF) and simulated intestinal fluid (SIF). The results showed that the SGF or SIF treatments of the citrus peels did not significantly increase the total phenolic content (TPC) or total flavonoid content (TFC), except for that of the TFC of ponkan p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…Natural antioxidants such as vitamins, carotenes, minerals, or fiber are not supposed to be the only components responsible for the antioxidant properties of fruit (Chuyen, Roach, Golding, Parks, & Nguyen, 2017;Sungsinchai, Niamnuy, Jaree, & Devahasti, 2017). In previous research, the significant correlations have been reported between phenolic contents and antioxidant capacities (Su et al, 2017;Zhuang, Ma, Guo, & Sun, 2017). There is strong evidence that the phenolic compounds could be significantly bioavailable and even more powerful than antioxidants as vitamin C, E in vitro (Scalbert, Manach, Morand, R em esy, & Jim enez, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Natural antioxidants such as vitamins, carotenes, minerals, or fiber are not supposed to be the only components responsible for the antioxidant properties of fruit (Chuyen, Roach, Golding, Parks, & Nguyen, 2017;Sungsinchai, Niamnuy, Jaree, & Devahasti, 2017). In previous research, the significant correlations have been reported between phenolic contents and antioxidant capacities (Su et al, 2017;Zhuang, Ma, Guo, & Sun, 2017). There is strong evidence that the phenolic compounds could be significantly bioavailable and even more powerful than antioxidants as vitamin C, E in vitro (Scalbert, Manach, Morand, R em esy, & Jim enez, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Digestion and absorption of the lotus leaf will be affected by pH, digestive enzymes, inorganic salts and other physiological factors (Bouayed et al, 2011). The in vitro simulated gastric and intestinal digestions are widely used for a preliminary assessment of the effect of digestion (Moomand & Lim, 2015;Kamiloglu et al, 2017;Su et al, 2017). Researchers have provided contradictory information that the phenolic content and antioxidant activity of fruits, vegetables and cereals may either be increased (Tagliazucchi et al, 2010) or reduced after digestion (Bao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The ABTS value was detected using the method reported previously (Su et al, 2017). The absorbance values were measured on an ultraviolet spectrophotometer at 734 nm.…”
Section: Tpc ¼mentioning
confidence: 99%
“…Several researchers have studied the changes of the content of active components and antioxidant properties after the simulated digestion of fruits, vegetables and agro-industrial co-products. For instance, Su et al investigated the effects of simulated gastric fluid (SGF) and simulated intestinal fluid (SIF) on the phenolic contents and antioxidant activities of three different varieties of citrus peels and found that in vitro simulated digestion did not significantly increased the total phenolic content or total flavonoid content but did improve antioxidant activities (Su et al, 2017). Similarly other research has shown that the SGF and SIF digestions could significantly increase the total phenolic content of lotus leaf, but had different effects on the FRAP and ABTS antioxidant activities (Su et al, 2018).…”
Section: Introductionmentioning
confidence: 99%